Responsible Business Professionals A Strategic Perspective of the Global Challenges. - Kar, Rabi Narayan (Cambridge Scholars Publisher, 2020)
This collection of essays explores contemporary reflections on responsible business knowledge and proactive management competences for the growing bilateral trade between India and other countries in the global context. It offers discussions on how responsible business professionals (RBPs) from multinational enterprises (MNEs) play a crucial role in creating the responsible infrastructure of a business ecosystem. The book also delves into business ecosystems, the development of responsible leadership, and managing cross-cultural communication. It represents a significant intervention in underl.